Efektivitas Kode Etik Notaris dalam Memberikan Pelayanan Jasa Kepada Klien - Setyowati, Dewi; Huda, Miftakhul (UNES Law Review, 2024)
The code of ethics in the notary profession is not just a set of rules or codes of conduct, but also reflects the essence of integrity and responsibility that a notary must have. In providing services to clients, a notary not only acts as a legal professional, but also as a guardian of trust and legal certainty for the community. Therefore, it is important for notaries to understand and abide by their code of ethics conscientiously. The research method used is normative legal research. With a statutory approach, i.e. examining current laws and regulations, other relevant literature, and case studies related to the research topic. The results showed that the Code of Ethics is important for notaries in providing services to clients, maintaining integrity and professionalism. However, there are still cases of violations that harm the reputation of the profession. To prevent this, it is necessary to increase supervision, education, and training for notaries. Transparency and accountability in handling violations are also important. Public awareness of the importance of choosing notaries who comply with the code of ethics should also be increased through information campaigns. These steps are expected to ensure that notary services remain of high quality and trust.